Biphasic response in number of stem cells and endothelial progenitor cells after left ventricular assist device implantation: A 6 month follow-up. (1st September 2016) - Ivak, Peter; Pitha, Jan; Wohlfahrt, Peter; Kralova Lesna, Ivana; Stavek, Petr; Melenovsky, Vojtech; Dorazilova, Zora; Hegarova, Marketa; Stepankova, Jitka; Maly, Jiri; Sekerkova, Alena; Turcani, Dominika; et al.
Abstract: Background: Continuous blood flow could have deleterious effects on endothelium and vascular health. This could have serious consequences in patients with heart failure treated with continuous flow left ventricular assist devices (LVAD). Therefore, we studied effect of LVAD on three circulating vascular biomarkers: stem cells (SC), endothelial progenitor cells (EPC) and microparticles (MP). Methods: In 23 patients (5 women) with end-stage heart failure, SC, EPC and MP were measured before, and 3 and 6 months after implantation of LVAD (HeartMate II). SC were defined using determination of surface antigen expression as mononuclear CD34 +/CD45low + cells and EPC as mononuclear CD34 +/CD45low +/KDR + cells. MP concentrations were determined by ELISA method. Results: Three months after LVAD implantation numbers of SC and EPC significantly decreased (p = 0.01 and p = 0.001, respectively). On the contrary, between 3rd and 6th month after implantation they significantly increased (p = 0.006 and p = 0.003, respectively).MP did not change significantly during the study despite exerting similar trend as SC and EPC. Conclusions: Observed biphasic changes of SC and EPC might reflect two processes. First, shortly after LVAD implantation, improved tissue perfusion could lead to decrease in ischemic stimuli and ensuing decrease of SC and EPC. Second, continuous flow between 3rd and 6th month produced by LVAD could lead to increase of SC and EPC through activation of endothelium. This explanation could be supported also by similar trend in the changes of concentrations of MP.